The Mennonite farmer: a global history of place and sustainability - Royden, Loewen (Young center books in anabaptist and pietist studies, 2021)
"This book is based on a multiyear study of seven Anabaptist communities around the world: in Bolivia, Canada, Indonesia, the Netherlands, Russia, the United States, and Zimbabwe. The author uncovers shared commitments to place and sustainable community, notwithstanding the differences that distinguish the locales culturally and environmentally"--